A comparative analysis of experienced uncertainties in relation to risk communication during COVID19: a four-country study - Cristea, Florin; Weishaar, Heide; Geurts, Brogan; Delamou, Alexandre; Tan, Melisa Mei Jin; Legido-Quigley, Helena; Aminu, Kafayat; Mari-Sáez, Almudena; Rocha, Carlos; Camara, Bienvenu; Barry, Lansana; Thea, Paul; et al. (Globalization and health, 2022)
During outbreaks, uncertainties experienced by affected communities can influence their compliance to government guidance on public health. Communicators and authorities are, hence, encouraged to acknowledge and address such uncertainties. However, in the midst of public health crises, it can become difficult to define and identify uncertainties that are most relevant to address. We analyzed data on COVID-19-related uncertainties from four socio-economic contexts to explore how uncertainties can influence people's perception of, and response to Risk Communication and Community Engagement (RCCE) strategies. This qualitative study, which adopts an interpretative approach, is based on data from a documentary review, key informant interviews (KII), and focus group discussions (FGD) with members of the general public and people with barriers to information from Germany, Guinea, Nigeria, and Singapore. Transcripts from the KII and FGD were coded and analyzed thematically. We interviewed a total of 155 KIs and conducted 73 FGD. Our analysis uncovered a divergence between uncertainties deemed relevant by stakeholders involved in policy making and uncertainties that people reportedly had to navigate in their everyday lives and which they considered relevant during the pandemic. We identified four types of uncertainties that seemed to have influenced people's assessment of the disease risk and their trust in the pandemic control strategies including RCCE efforts: epidemiological uncertainties (related to the nature and severity of the virus), information uncertainties (related to access to reliable information), social uncertainties (related to social behavior in times of heightened risk), and economic uncertainties (related to financial insecurities). We suggest that in future outbreaks, communicators and policy makers could improve the way in which affected communities assess their risk, and increase the trust of these communities in response efforts by addressing non-epidemiological uncertainties in RCCE strategies.